PREVALENCE OF GINGIVITIS AMONG PREGNANT AND NON-PREGNANT WOMEN - Bareera Rezvi, Fathima; Rajasekar, Arvina; Chaudhary, Manjari (International Journal of Psychosocial Rehabilitation, 2020)
Good oral health is important across a person's lifespan. Pregnancy is a transient physiological state which brings about different hormonal changes in a woman's body, which lead to changes in the oral cavity. These changes have important implications as they have been known to cause adverse pregnancy outcomes. This study aims to evaluate the prevalence of gingivitis among pregnant and non-pregnant women. This retrospective study was done by analyzing the case records of 300 patients in a private institution between June 2019- March 2020. Out of 300 patients, 150 were pregnant and 150 were non-pregnant. Data regarding their periodontal status was collected from the case records and analyzed. Descriptive statistics and inferential statistics were done using SPSS Software, Version 23. Pregnant women had a higher prevalence of gingivitis (40.3%) and periodontitis (6.0%). Whereas most of the non-pregnant women had clinically healthy gingiva (30%). The association between periodontal status and the pregnancy status was statistically significant. In age wise assessment, prevalence of clinically healthy gingiva (15.7%), gingivitis (28.7%) and periodontitis (3.3%) were high among the 26–30-year-old patients, however the association between different age groups and the periodontal status was statistically not significant. The present study suggested that pregnant women had a higher prevalence of gingivitis and periodontitis and was more common within the age group of 26-30 years.